2022
DOI: 10.3390/prosthesis4020015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy between Denture Bases Produced by Subtractive and Additive Manufacturing Methods: A Pilot Study

Abstract: Today, two different types of CAD-CAM fabrication methods for complete denture bases are available besides the conventional protocols: a subtractive milling process from a prepolymerized block of polymethylmethacrylate and an additive manufacturing process that built the denture base using a light-cured liquid in a VAT-polymerization process. The aim of this study was to evaluate and to compare the accuracy and precision of denture prosthetic bases made with subtractive and additive manufacturing technologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This type of dental resins facilitates the production of denture bases by easy milling [4]. Despite these advantages, the following disadvantages exist for PMMA: hypersensitivity, color changes over time, abrasion, and porosity [5]. Another limitation is the monochromatic and unesthetic teeth, which some manufacturers have overcome by using a unique layering system, resulting in polychromatic teeth that simulate the dentin and enamel of natural teeth, providing premium esthetics [6].…”
Section: Introductionmentioning
confidence: 99%
“…This type of dental resins facilitates the production of denture bases by easy milling [4]. Despite these advantages, the following disadvantages exist for PMMA: hypersensitivity, color changes over time, abrasion, and porosity [5]. Another limitation is the monochromatic and unesthetic teeth, which some manufacturers have overcome by using a unique layering system, resulting in polychromatic teeth that simulate the dentin and enamel of natural teeth, providing premium esthetics [6].…”
Section: Introductionmentioning
confidence: 99%
“…11 However, subtractive production of dentures produces large amounts of waste and requires a vast amount of raw material. 12 On the other hand, 3D-printing of a dental prosthesis is accomplished by layering of the material. Therefore, it is considered less expensive than milling due to reduced material waste and absence of wear of milling tools.…”
mentioning
confidence: 99%
“…Additionally, a number of studies reported that milled CAD‐CAM fabricated specimens present superior color stability compared to heat‐, self‐, and light‐cured acrylics 10 or 3D‐printed acrylic resin 11 . However, subtractive production of dentures produces large amounts of waste and requires a vast amount of raw material 12 . On the other hand, 3D‐printing of a dental prosthesis is accomplished by layering of the material.…”
mentioning
confidence: 99%
“…The findings of Vallittu et al showed that the increased amount of water sorption could be caused by the printed layering technique [50]. The absorbed water enters between the layers into the resin's polymer; thus, the interpolymeric spaces are filled with water, which penetrates the empty spaces and voids, forcing the polymer chain away from other chains [51][52][53][54]. This theory was confirmed using the method of electron microscopy [55].…”
Section: Discussionmentioning
confidence: 96%